ARTIFICIAL INTELLIGENCE AS A GAME-CHANGER IN INVESTMENT DECISIONS: A FINANCIAL LITERACY PERSPECTIVE (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Artificial Intelligence (AI) has a significant impact on human life today. The application of AI in the financial sector indirectly influences investors in their decision-making processes. Based on this phenomenon, this study aims to analyze whether AI can assist individuals in making investment decisions based on their level of financial literacy. Additionally, this research explores how investors can effectively adopt technology particularly AI as applied within the financial field. The study targets members of Indonesia’s Generation Z who are already engaged in investing. Out of 300 respondents initially surveyed, 241 valid responses were obtained. The research method employs descriptive analysis, and the hypotheses are tested using the Structural Equation Model (SEM) approach with Partial Least Squares (PLS), facilitated by SmartPLS software. The results indicate that financial literacy significantly influences investment decisions. However, AI does not moderate the relationship within the proposed research model.